Religious Personality and Smoking among Form Two Students in Rural Schools in Malacca, Malaysia - MZ, Nor Afiah; MA, Rahmah; MS, Salmiah; I, Fazilah; S, Shamsul Azhar (IIUM Medical Journal Malaysia, 2012)
Introduction: There is an increasing trend in smoking among rural adolescents compared to urban adolescents in Malaysia. This study was to determine the relationship between religious personality and smoking among form two students from the rural schools in Malacca. Methods: This was an unmatched case-control study conducted from May 2010 to August 2010 among form two school children from rural area in Malacca. There were 484 cases, and 444 controls selected using randomized cluster sampling. The dependent variable was smoking, and the independent factors were religious personality. Validated and reliability-tested questionnaires were used for data collection. Results: The mean age (year) at which smoking was first tried among the cases was 11.39 + 2.107. There were eleven out of twenty three significant differences between religious personality statements in the cases and control group. Those were: reciting the Quran/Holy book/Scriptures even when busy, making efforts to deepen the understanding of the religion, trying to understand the teachings of the religion in the Holy book/Quran, inviting others to perform solat/prayer/religious service, making sure all the family members are following the teachings according to the religion, referring to the learned people when feeling uncertain about the rulings/teachings of the religion, performing work duties enthusiastically because of the religion/God, making efforts to remember death and afterlife often, making efforts to internalize the ethical conduct of the religion in daily life, setting aside money every year for religious purposes and looking for opportunities to give charity. Conclusion: Religious personality is an important factor which may influence adolescents volved in smoking.